Co-Processed Laktosa-Metilselulosa Sebagai Zat Tambahan Tablet Dengan Metode Kempa Langsung - Mursyid, A. Mumtihanah; -, Nurlina; Mustakim, Musfira (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2017)
ABSTRAK Co-processing is a technique to obtain a new excipient by combined two or more excipients with an appropriate process. Excipient by co-processing can improve the properties of excipient. The purpose of this research is to produce an excipient with good properties by co-processed Lactosa-Methylcellulosa, so that it is can be use as an excipient for direct compression tablet. This research was compared co-processed Lactosa-Methylcellulosa fabricated by wet milling technique. The co-processed material obtained were evaluated; particle size distribution, average diameter, density, porosity, carr’s index, flowability,compactibility and DSC. And they have been compared with their’s physical mixture. The flowability of co-processed Lactosa-Methylcellulosa was increasedbased on measurement by angles of reposewho did’nt passed 25o, in the range of 16.16 ± 0.63 to 18.59 ± 1.29 and the tensile strength of co-processed Lactosa-Methylcellulosa was increased until 1.79 MPa was higher than it’s physical mixturewere not can be measured tensile strength because the tablet not be able to be developed whole.DSC result of co-processed had similiar pattern with Lactosa. The co-processed Lactosa-Methylcellulosa is more promising to use as direct compression material.